Cooperative strategic games - Elon Kohlberg; Abraham Neyman (Theoretical Economics, 2021)
The value is a solution concept for n-person strategic games, developed by Nash, Shapley, and Harsanyi. The value of a game is an a priori evaluation of the economic worth of the position of each player, reflecting the players' strategic possibilities, including their ability to make threats against one another. Applications of the value in economics have been rare, at least in part because the existing definition (for games with more than two players) consists of an ad hoc scheme that does not easily lend itself to computation. This paper makes three contributions: We provide an axiomatic foundation for the value; exhibit a simple formula for its computation; and extend the value-its definition, axiomatic characterization, and computational formula-to Bayesian games. We then apply the value in simple models of corruption, oligopolistic competition, and information sharing.
Keywords: C71; C72; C78; 330; Strategic games; cooperative games; shapley value; nash variables threats; bribery